Advances and trends of non-marine shale sedimentology: A case study from Gulong Shale of Daqing Oilfield, Songliao Basin, NE China - Longde SUN; Rukai ZHU; Tianshu ZHANG; Yi CAI; Zihui FENG; Bin BAI; Hang JIANG; Bo WANG (Petroleum Exploration and Development)
This study took the Gulong Shale in the Upper Cretaceous Qingshankou Formation of the Songliao Basin, NE China, as an example. Through paleolake-level reconstruction and comprehensive analyses on types of lamina, vertical associations of lithofacies, as well as stages and controlling factors of sedimentary evolution, the cyclic changes of waters, paleoclimate, and continental clastic supply intensity in the lake basin during the deposition of the Qingshankou Formation were discussed. The impacts of lithofacies compositions/structures on oil-bearing property, the relation between reservoir performance and lithofacies compositions/structures, the differences of lithofacies in mechanical properties, and the shale oil occurrence and movability in different lithofacies were investigated. The insights of this study provide a significant guideline for evaluation of shale oil enrichment layers/zones. The non-marine shale sedimentology is expected to evolve into an interdisciplinary science on the basis of sedimentary petrology and petroleum geology, which reveals the physical, chemical and biological actions, and the distribution characteristics and evolution patterns of minerals, organic matter, pores, fluid, and phases, in the transportation, sedimentation, water-rock interaction, diagenesis and evolution processes. Such research will focus on eight aspects: lithofacies and organic matter distribution prediction under a sequence stratigraphic framework for non-marine shale strata; lithofacies paleogeography of shale strata based on the forward modeling of sedimentation; origins of non-marine shale lamina and log-based identification of lamina combinations; source of organic matter in shale and its enrichment process; non-marine shale lithofacies classification by rigid particles + plastic components + pore-fracture system; multi-field coupling organic-inorganic interaction mechanism in shale diagenesis; new methods and intelligent core technology for shale reservoir multi-scale characterization; and quantitative evaluation and intelligent analysis system of shale reservoir heterogeneity.